2011
DOI: 10.1007/s11270-010-0728-y
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of Coastal Aquifers Due to Nutrient Pollution from Agriculture: Kalpitiya, Sri Lanka

Abstract: This study focuses on spatial and temporal nutrient pollution of groundwater in the unconfined sandy aquifers of Kalpitiya peninsula, Sri Lanka, where agricultural activities are intense. The study covers two consecutive dry and rainy seasons during the period from 2008 to 2010. Nitrate is the dominant nutrient pollutant in groundwater. The values of Nitrate-N contents ranged from 0.60 to 212.40 mg/L in the dry seasons and 0.20-148.50 mg/L in rainy seasons. Phosphate in groundwater ranged from 0.20 to 5.70 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 40 publications
2
17
0
Order By: Relevance
“…In the islands off the peninsulas, 50 % of the wells contained nitrate levels above 10 mg/l. Other studies have found high levels of nitrate-N in groundwater (Mikunthan and de Silva 2009;Jeyaruba and Thushyanthy 2009), which have been directly related to agricultural activities ( (Jayasingha et al 2011;Liyanage et al 2000); Kuruppuarachchi and Fernando 1999;(Nagarajah et al 1988)). Overextraction of groundwater resources has also contributed to saltwater intrusion and higher nitrate loads in the groundwater (Jayasekera et al 2011;Jayasekera 2007).…”
Section: Introductionmentioning
confidence: 94%
“…In the islands off the peninsulas, 50 % of the wells contained nitrate levels above 10 mg/l. Other studies have found high levels of nitrate-N in groundwater (Mikunthan and de Silva 2009;Jeyaruba and Thushyanthy 2009), which have been directly related to agricultural activities ( (Jayasingha et al 2011;Liyanage et al 2000); Kuruppuarachchi and Fernando 1999;(Nagarajah et al 1988)). Overextraction of groundwater resources has also contributed to saltwater intrusion and higher nitrate loads in the groundwater (Jayasekera et al 2011;Jayasekera 2007).…”
Section: Introductionmentioning
confidence: 94%
“…Nitrogen (N) enrichment is responsible for the deterioration of water quality and health hazards (World Health Organization, ; Gelberg et al ., ; Gulis et al ., ), such as eutrophication (Howarth and Marino, ; Jayasingha et al ., ) and algal growth (Linderfelt and Turner, ).…”
Section: Introductionmentioning
confidence: 99%
“…Groundwater contamination in terms of nitrate pollution in the area has been studied for several decades (Lawrence & Kuruppuarachchi, 1986;Mubarak et al, 1992;Kuruppuarachchi & Fernando, 1999;Liyanage et al, 2000). Recent investigations revealed that nitrate levels in groundwater at some places in Kalpitiya agricultural fields is as high as 212 mg/L during dry periods and more than 50 % of the studied wells have nitrate levels exceeding the WHO allowable limits (Jayasingha et al, 2011). It was also found that the nitrate accumulation rate is 2.3 mg/L per year for the last 10 year period.…”
Section: June 2013mentioning
confidence: 99%
“…The Kalpitiya agricultural field is an active and dynamic environment because the area is extensively fertilized and intensively watered (Jayasingha et al, 2011). Despite the semi arid conditions of the area, the sandy soil of the agricultural areas retains soil moisture for a considerable period during daytime due to watering.…”
Section: Nitrate Retention In Sands Mixed With Claymentioning
confidence: 99%